THE RELATIONSHIP OF NATIONAL CRAFTS WITH EDUCATION (Modern American Journal of Social Sciences and Humanities, 2026)
National crafts are an important socio-cultural phenomenon that embodies the centuries-old history, culture and aesthetic views of the people. It is of particular importance not only as a type of economic activity, but also as a means of preserving national identity and passing it on from generation to generation. In this regard, the issue of developing national craft traditions among young people is of urgent scientific and practical importance today. First of all, the development of craft traditions among young people is an important factor in preserving national heritage. In the context of globalization, many national craft traditions are at risk of extinction. In particular, we are witnessing in today's real life that traditional textiles, woodcarving, crafts based on natural materials, pottery and traditional tableware are under threat of weakening. Scientific research shows that the types of crafts that are most at risk in the context of globalization are those that are based on manual labor, require a lot of time and skill, and are dependent on natural resources. Their loss leads not only to economic, but also to cultural and civilizational losses. Therefore, education and state support are of great importance for preserving these traditions. By involving young people in crafts, they develop a sense of national identity, historical memory, and respect for cultural heritage. This, in turn, serves to ensure spiritual stability in society. Crafts are an effective means of ensuring youth employment and increasing their economic activity. In modern market conditions, the demand for products based on manual labor is increasing. Products created using national patterns, traditional styles, and natural materials are competitive not only in the domestic but also in the foreign market.